If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(5x) + -1ln(5) + 3ln(x) = 0 Remove parenthesis around (5x) ln * 5x + -1ln(5) + 3ln(x) = 0 Reorder the terms for easier multiplication: 5ln * x + -1ln(5) + 3ln(x) = 0 Multiply ln * x 5lnx + -1ln(5) + 3ln(x) = 0 Reorder the terms for easier multiplication: 5lnx + -1 * 5ln + 3ln(x) = 0 Multiply -1 * 5 5lnx + -5ln + 3ln(x) = 0 Multiply ln * x 5lnx + -5ln + 3lnx = 0 Reorder the terms: -5ln + 5lnx + 3lnx = 0 Combine like terms: 5lnx + 3lnx = 8lnx -5ln + 8lnx = 0 Solving -5ln + 8lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(-5 + 8x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5 + 8x)' equal to zero and attempt to solve: Simplifying -5 + 8x = 0 Solving -5 + 8x = 0 Move all terms containing l to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 8x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 8x = 0 + 5 8x = 0 + 5 Combine like terms: 0 + 5 = 5 8x = 5 Add '-8x' to each side of the equation. 8x + -8x = 5 + -8x Combine like terms: 8x + -8x = 0 0 = 5 + -8x Simplifying 0 = 5 + -8x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 14-4x=-6-6(8x+4) | | (100+10)9= | | 2x+1=3+y | | 18.9+c=31.2 | | 5(x+7)=8 | | 21Y-8Y(2)=6Y+1-10 | | 23-7+4(x-1)=11 | | 8y-3y+6=-10 | | x*.10=14.79 | | 27r^3+1=0 | | 19-2x-3=2x+6+x | | 7x-15=2x+10 | | 3x^2+7x+2=y | | 5x+12+6x=93+2x | | h=-10t^2+90 | | 3x-1=2x+2+1 | | 3x^3+25x^2+28x=0 | | 4(n+2)=9n-7 | | 2y-1+y=-2+13-2y | | x+y=-400 | | 4x+2x-60=48 | | 2p-10-2=12-p-p | | r^3+3r^2=0 | | v+1-2v=4 | | 3n+15=7n-1 | | 4+3n+2=-9 | | y=2cos(3x+1) | | -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t |